OSCON Open Source Software Superstream Series Live Coding-Go, Rust, and Python - Körbes, Ellen; Tran, Tara; Butt, Mehreen; Walicki, John; Stocks, Nathan; Milinkovich, Mike; Lerner, Reuven; Hightower, Kelsey; Roumeliotis, Rachel (O'Reilly Media, Inc., 2020)
This three-part series of half-day online events gives attendees an overarching perspective of software development from which to make decisions that strengthen and grow companies and industries, a deep knowledge of key open source technologies to make it happen, and a community in which both they and their companies can thrive. In Part 1, Live Coding-Go, Rust, and Python, we wanted to get deeper into actual coding, and one way to do that was to outlaw slides. That's right, these sessions all incorporate live-coding. These four sessions from Ellen Körbes, John Walicki, Nathan Stocks, and Reuven Lerner will walk you through coding best practices and new ways of getting the most out of languages like Python, Go, and Rust. This event is sponsored by IBM, and features spotlights on Kode With Klossy and the Eclipse Foundation. About the presenters: Rachel Roumeliotis is vice president of content strategy at O'Reilly, where she leads an editorial team that covers a wide variety of programming topics ranging from full stack to open source in the enterprise to emerging programming languages. She's been a programming chair for the O'Reilly OSCON, Fluent, Strata, Software Architecture, and Security Conferences. She's currently the programming chair for the OSCON and Strata Data & AI Superstream Series on O'Reilly online learning. She's been working in technical publishing for 10 years, acquiring content in many areas including mobile programming, UX, computer security, and AI. Kelsey Hightower has worn every hat possible throughout his career in tech and enjoys leadership roles focused on making things happen and shipping software. Kelsey is a strong open source advocate focused on building simple tools that make people smile. When he isn't slinging Go code, you can catch him giving technical workshops covering everything from programming to system administration. Ellen Körbes ran DevRel at both Tilt and Garden-two of the very few companies 100% focused on the development experience side of Kubernetes. They got their start building Kubernetes CLI tooling under SIG-CLI. They've since spoken about Go and Kubernetes at many world-famous events. Tara Tran is the manager of recruitment and instruction, and Mehreen Butt is an instructor at Kode With Klossy. John Walicki is the CTO for edge/IoT advocacy in the Developer Ecosystem Group within the IBM Cognitive Applications Group, where he helps developers create custom IoT and embedded Linux solutions for thei...
Online resource; Title from title screen (viewed June 24, 2020)
Keywords: Internet videos; Streaming video; Vidéos sur Internet; Vidéo en continu; streaming video; Electronic videos